Multi-response optimization of EDM drilling parameters of the Nitinol SMA - Amiya Kumar Sahoo; Praneet Pandey; Dhananjay R. Mishra (The Journal of Engineering and Exact Sciences)
The demand for Nitinol (SMA) is increasing rapidly for various applications. With the aim of optimum control parameters of EDM, 46 experiments completed on six specimens of 6.156 mm thickness using Sparkonix EDM drill machine. Current (I), voltage (V), charging-time (TON), discharging-time (TOFF), and dielectric pressure (DP) were taken as input control parameters. Single-indexed optimization of material removal rate (MRR), tool-wear rate (TWR), and degree of tapperness (DoT) are evaluated using gray relational grade (GRG). Individual control-parameter contributions are evaluated using Taguchi and ANOVA. The obtained optimal input control parameters were used for the confirmation experiment, and the obtained result gives good agreement to it. V and TON are found as the most significant parameters. Maximum and minimum values of MRR, TWR, and DoT have been recorded as 0.0277 & 0.0074 g/min, 0.0177 & 0.0033 g/min, and 0.032 & 0.01 radians respectively. MRR, TWR, and DoT improved by 49.1, 4.5, and 43.3 %, respectively.